Malignant hypertension in women of childbearing age and its relation to the contraceptive pill. Issue 6579 (25th April 1987) - Lim, K G; Isles, C G; Hodsman, G P; Lever, A F; Robertson, J W
Abstract : Eleven of 34 women aged 15-44 with malignant phase hypertension were taking oral contraceptives at presentation. All had had normal blood pressure before starting to take the pill. In four the interval between the start of oral contraception and the diagnosis of malignant hypertension was less than four months, and in eight no other cause for the hypertension was found. Underlying renal disease and renal failure were less common among pill users than among non-users with malignant hypertension who were of similar age. No pill user became normotensive after withdrawal of the pill, but blood pressure was well controlled (diastolic less than 90 mm Hg) in three patients taking only one drug. By contrast, all 23 non-users needed two or more antihypertensive drugs to control blood pressure. Ten year survival was 90% among pill users and 50% among non-users. These results suggest that oral contraceptives may be a common cause of malignant hypertension in women of child-bearing age. If the pill is stopped and underlying renal disease excluded the long term prognosis for such patients is excellent.